Perspectives of the Modification of the Tax Burden in the Hotel and Restoration Industry, in the Context of Tax Pressure Generated by GEO No. 16/2022 - Razvan Vonea (Agora International Journal of Economical Sciences (AIJES), 2022)
The proposed Article sets out the tax burden on economic entities operating in the hospitality industry in terms of income taxation. We have presented theoretical legislative aspects regarding the specific tax trim, which remains in its full action until the end of the financial year 2022, but also illustrative examples that provide accurate information on the fiscal pressure felt by these economic operators. The prospect of increasing tax pressure in this industry is becoming clearer, following the amendment of the primary legislation in the field of taxation of these economic operators. Thus, the idea of applying the tax specific to these activities is abandoned by shifting to another form of income tax.
Keywords: 330